\(\Leftrightarrow\sqrt[3]{3x+1}+\sqrt[3]{2x-9}=\sqrt[3]{x-5}+\sqrt[3]{4x-3}\)
Đặt \(\sqrt[3]{3x+1}=a;\sqrt[3]{2x-9}=b;\sqrt[3]{x-5}=c;\sqrt[3]{4x-3}=d\) ta được hệ:
\(\left\{{}\begin{matrix}a+b=c+d\\a^3+b^3=c^3+d^3\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}a+b=c+d\\\left(a+b\right)^3-3ab\left(a+b\right)=\left(c+d\right)^3-3cd\left(c+d\right)\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}a+b=c+d=0\\\left[{}\begin{matrix}a+b=c+d\ne0\\ab=cd\end{matrix}\right.\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}a^3+b^3=0\\a^3b^3=c^3d^3\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}5x-8=0\\\left(3x+1\right)\left(2x-9\right)=\left(4x-3\right)\left(x-5\right)\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}5x-8=0\\x^2-x-12=0\end{matrix}\right.\)
\(\Leftrightarrow...\)